Preparation and Characterization of Polyvinyl Acetate (Kollidon® SR) Microspheres Containing Diclofenac Sodium I: Effect of Stirring Rate and Total Solid Content (Dhaka University Journal of Pharmaceutical Sciences, 2010)
Microspheres were prepared by W/O emulsification solvent evaporation technique where Diclofenac Sodium (DS) and Kollidon® SR (KSR) were used as model drug and polymer respectively. Light liquid paraffin (LLP) was used as oil phase and 1% (w/w of the continuum) of span 60 was used for emulsification. Microspheres were prepared using different stirring rate (1500, 2000, 2500, 3000 rpm) and different total solid content of the system (0.08%, 0.16%, 0.24% w/w of the continuum). Microsphere morphology was examined with the help of Scanning Electron Microscope (SEM) and particle size distribution was analyzed by Mastersizer 2000. Larger microspheres were obtained with decreasing stirring rate. Increase in solid content of the system also increased microsphere size. Drug loading was also found to be affected due to these preparative variables. In vitro dissolution study was performed in a USP XXX paddle apparatus (type 2). Dissolution media was buffer of pH 7.2, paddle speed was 50 rpm and dissolution temperature was maintained at 37 ± 0.5°C. Release of DS from KSR microspheres was found to follow higuchi mechanism. DS release was increased with increased stirring rate. But increased solid content of the system resulted in reduced release of DS. Normalized release rate of DS was also found to be affected by these preparative variables. Release rates were found increased with increased stirring rate whereas rates were found decreased with increased solid content of the system. Key words: Kollidon® SR; Diclofenac Sodium; Microsphere; Solvent evaporation technique. 10.3329/dujps.v8i2.6024 Dhaka Univ. J. Pharm. Sci. 8(2): 111-116, 2009 (December)